Obesogens: How They Are Identified and Molecular Mechanisms Underlying Their Action - Mohajer, Nicole; Du, Chrislyn Y.; Checkcinco, Christian; Blumberg, Bruce (Frontiers in Endocrinology, 2021)
Adult and childhood obesity have reached pandemic level proportions. The idea that caloric excess and insufficient levels of physical activity leads to obesity is a commonly accepted explanation for unwanted weight gain. This paradigm offers an insufficient explanation for the worldwide pandemic of obesity. Endocrine disrupting chemicals (EDCs) are chemicals that resemble natural hormones and disrupt endocrine function by interfering with the function of endogenous hormones. EDCs are widespread in our environment and contaminate food, water and personal care products, which together cause the bulk of human exposures. A subset of EDCs called obesogens have been found to cause metabolic disruptions such as increased fat storage, in vivo. Obesogens act through multiple avenues and have been found to affect adipose cell commitment, differentiation, hepatic function and the gut microbiome, among other effects. The rising prevalence of obesity and its comorbidities demands increased attention to identifying obesogens and enabling preventive strategies to ensure the public health and that of future generations. This review addresses current findings on known obesogens and their effects on the metabolic system, the mechanisms through which they act upon, and the screening efforts that have identified them.